Antimicrobial resistance, virulence determinants and genetic profiles of clinical and nonclinical Enterococcus cecorum from poultry. (7th January 2015) - Jackson, C.R.; Kariyawasam, S.; Borst, L.B.; Frye, J.G.; Barrett, J.B.; Hiott, L.M.; Woodley, T.A.
Abstract Enterococcus cecorum has been implicated as a possible cause of disease in poultry. However, the characteristics that contribute to pathogenesis of Ent. cecorum in poultry have not been defined. In this study, Ent. cecorum from carcass rinsates (n = 75) and diseased broilers and broiler breeders (n = 30) were compared based upon antimicrobial resistance phenotype, the presence of virulence determinants and genetic relatedness using pulsed‐field gel electrophoresis (PFGE). Of the 16 antimicrobials tested, Ent. cecorum from carcass rinsates and clinical cases were resistant to ten and six of the antimicrobials, respectively. The majority of Ent. cecorum from carcass rinsates was resistant to lincomycin (54/75; 72%) and tetracycline (46/75; 61·3%) while the highest level of resistance among clinical Ent. cecorum was to tetracycline (22/30; 73·3%) and erythromycin (11/30; 36·7%). Multidrug resistance (resistance to ≥2 antimicrobials) was identified in Ent. cecorum from carcass rinsates (53/75; 70·7%) and diseased poultry (18/30; 60%). Of the virulence determinants tested, efaAfm was present in almost all of the isolates (104/105; 99%). Using PFGE, the majority of clinical isolates clustered together; however, a few clinical isolates grouped with Ent. cecorum from carcass rinsates. These data suggest that distinguishing the two groups of isolates is difficult based upon the characterization criteria used. Significance and Impact of the Study In this study, antimicrobial resistance phenotype, virulence gene profile and genetic relatedness of Enterococcus cecorum isolated from diseased broiler chickens and poultry carcass rinsates were determined. The majority of isolates from both groups were multidrug resistant and harboured few virulence determinants. Results from this study suggest that clinical Ent. cecorum and Ent. cecorum from poultry carcass rinsates may share a common genetic background; clinical Ent. cecorum possess virulence determinants that have not been previously described for this species. Elucidation of those unknown virulence determinants is important for understanding the pathogenesis of Ent. cecorum infections in poultry.